2021
DOI: 10.18355/xl.2021.14.03.15
|View full text |Cite
|
Sign up to set email alerts
|

Magic in healing practice: a case study in Vietnam and its philosophical assessment

Abstract: The use of magic and religion in healing practices in Vietnam is relatively popular. In the folklore and folk religion of Vietnam, it is often said that “In case of sickness, follow any feasible cures [co benh thi vai tu phuong]” in the sense that all means, including using religious beliefs and rituals, will be used to get healing for oneself or one’s relatives. When people or their relatives get sick, besides going to medical facilities, they will look for a shaman, necromancer, monks, even priests, bishops,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The validity of this thesis is substantiated in studies of the social and psychological characteristics of users of social networks and their behavior in the Internet space (Golub & Lysenko, 2018;Belinskaya & Prilutskaya, 2019;Levin, 2020;Tugun et al, 2020;Nguyen et al, 2021;Zheltukhina et al, 2021;Begishev, Khisamova & Vasyukov, 2021a). It has been shown that social networks are the most important means of personal communication for the overwhelming majority of young people, attribution of certain parameters of social status (virtual social status) to a user by an outside observer (virtual social status) is associated with such personal characteristics of the user as neuroticism, Machiavellianism, narcissism, and self-monitoring.…”
Section: Introductionmentioning
confidence: 87%
“…The validity of this thesis is substantiated in studies of the social and psychological characteristics of users of social networks and their behavior in the Internet space (Golub & Lysenko, 2018;Belinskaya & Prilutskaya, 2019;Levin, 2020;Tugun et al, 2020;Nguyen et al, 2021;Zheltukhina et al, 2021;Begishev, Khisamova & Vasyukov, 2021a). It has been shown that social networks are the most important means of personal communication for the overwhelming majority of young people, attribution of certain parameters of social status (virtual social status) to a user by an outside observer (virtual social status) is associated with such personal characteristics of the user as neuroticism, Machiavellianism, narcissism, and self-monitoring.…”
Section: Introductionmentioning
confidence: 87%